Case report: quetiapine-induced transient elevation of activated partial thromboplastin time - Elghuwael, Ismail Mohamed Omar; Abdullah, Wan Ariffin (International Journal Development Research, 2020)
We report a case of 3-year old Pakistani boy who was previously well and brought to the hospital because of an accidental ingestion of quetiapine 8 hours before admission. No gastric lavage or activated charcoal done because of late presentation. He developed headache, excessive drinking and sleepiness few hours post ingestion but his symptoms resolved before arrival. His laboratory work up (Full blood count, blood urea and serum electrolytes, liver function test and coagulation profile) showed only an elevated activated Partial Thromboplastin Time (APTT). The patient was discharged after 24 hours. We checked APTTweekly. Even though, he remained well clinically his APTT continued to be high until after 1.5 months of ingestion when repeated APTT was normalized. Review at literature reported many anti-psychotics including quetiapine can cause an elevation of Prothrombin Time (PT) and APTT and low platelet count in adult patients taking them regularly [6], drug overdose can cause APTT elevation as well [4]. We conclude that this 3 years old child has quetiapine-induced transient elevation of APTT.